Influence of bankruptcy prediction and residual income on company share prices in various industry sectors - Shinta Disky Azzharah (Indonesian Journal of Islamic Economics Research, 2019)
Research use the panel data regression analysis model aims to determine the predictions of bankruptcy with the Altman Z-Score model and residual income influence the stock prices of companies listed in the Indonesian Syariah Stock Index (ISSI) in the period 2014 to 2018. Research This is a quantitative study using secondary data in the form of annual financial statements published by companies, with sampling using purposive sampling to obtain a sample of 23 manufacturing companies engaged in various industrial sectors. The research method uses the fixed effect model approach. The analysis said that the bankruptcy prediction using the Altman Z-Score model showed a significant negative effect on stock prices, while residual income had no effect on stock prices. In addition, the Altman Z-Score shows that many companies enter the gray area cut-off point and even go bankrupt, thus making shareholders reduce their share prices for the safety of their shares in the capital market.